Rasio Keuangan dan Arus Kas sebagai Prediktor Pembagian Dividen di Indonesia - Henny Setyo Lestari; Wahyuni Rusliyana Sari; Hartini Hartini; Adinda Putri Ramdhani (Postgraduate Program Merdeka University, 2021)
The purpose of this study is to determine the factors that influence the distribution of dividends in Indonesia. The objects of this research are 51 manufacturing companies listed on the Indonesia Stock Exchange for the 2015-2019 period. The method used is balanced panel data with random effects model. The results of this study are return on equity, cash flow, growth, and market to book value have a significant effect on the dividend payout ratio. While the variables of tax, current ratio, and institutional holding have no effect on the dividend payout ratio. The combination of financial ratios, cash flow, taxes, and institutional holding gives a new combination to this research. The contribution of this research is showed the fact that cash flow has a bigger role than profitability, while the sales will increase growth and stock prices will also increase thereby increasing dividend payments.DOI: https://doi.org/10.26905/afr.v4i2.6123